South Africa's economic response to the Covid-19 crisis: a post-pandemic shift or more of the same? - Sam Ashman; Ben Scully (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
Many observers see the Covid-19 crisis as marking a major shift in neoliberal globalization. We analyze this question from the perspective of South Africa. We argue that the 2020 crisis has not precipitated a major shift as much as it has rapidly accelerated trends which were already under way since 2008. We illustrate this through an account of political and economic developments in South Africa since 2008, showing how ongoing trends shaped the government's economic response to the Covid-19 crisis. We argue that the South African case illustrates broader trends in global capitalism. It suggests some significant departures from the version of neoliberal globalization that has prevailed in the past few decades. But on the fundamental question of the balance of economic power both between classes and between the global South and North, there is little reason for optimism.
Keywords: I18; L50; O55; P16; 330; Covid-19; South Africa; industrial policy; neoliberalism; energy transition